Retrospective observational study between robotic thyroidectomy via bilateral axillo-breast approach and conventional open surgery for thyroid cancer - Kuang, Fei; Zhou, Mengjia; Wang, Weiqin; Tian, Wen; Liu, Lin (Frontiers in Surgery, 2025)
BackgroundRobotic thyroidectomy has shown good acceptance results and improved cosmetic outcomes. This study aimed to evaluate the safety and efficacy of bilateral axillary-breast approach (BABA) robotic thyroidectomy compared with conventional open surgery for the treatment of thyroid cancer.MethodsThe clinicopathological features and surgical outcomes of 73 papillary thyroid cancer patients treated by robotic surgery using the BABA approach and 62 papillary thyroid cancer patients treated by open surgery in our department from January 2024 to January 2025 were analyzed and compared.ResultsThe operation time was longer in the robotic group than in the open surgery group (P = 0.001). However, when thyroid cancer requires lymph node dissection in the lateral neck area, the open operation time is longer than that of robotic surgery, although it is no significant (P > 0.05). The estimated blood loss was lower in the robotic group than in the open surgery group (P < 0.001). Both total number of removed lymph nodes (P = 0.019) and metastatic lymph nodes (P = 0.002) were higher in the robotic group than in the open surgery group. Postoperative inflammatory reaction was higher in the robotic group than in the open surgery group (P < 0.001). No significant difference was observed in the nerve injury or Chyle leakage between the two groups. No recurrence or metastasis was found.ConclusionsCompared with open surgery, BABA robot radical thyroid cancer surgery with lymph node dissection is safety and efficacy, and have advantages such as less intraoperative blood loss, no neck scar. Especially in lateral cervical lymph node dissection, robotic surgery has obvious advantages.